2016
DOI: 10.1016/s2215-0366(15)00436-8
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant augmentation with metyrapone for treatment-resistant depression (the ADD study): a double-blind, randomised, placebo-controlled trial

Abstract: Efficacy and Mechanism Evaluation (EME) programme, a UK Medical Research Council and National Institute for Health Research partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
0
37
0
1
Order By: Relevance
“…4 A recent UK RCT in patients with a similar degree of treatment resistance as in the patients in this study (mean MGHS score of 4.7), although with a lesser severity of depression (baseline mean MADRS score of 28), reported a 21% response rate and a 16% remission rate after 5 weeks in patients treated with placebo or metyrapone DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk augmentation of ongoing antidepressant treatment. 162 This suggests that patients in this study received considerable clinical benefit attributable to ECT treatment. However, the degree of improvement was less than is often reported with ECT; for example, Kellner et al 27 found a 65% remission rate with bilateral ECT, and a meta-analysis of seven cohort studies 8 found a 65% remission rate for patients without previous pharmacotherapy failure and a 48% remission rate for those with treatment resistance.…”
mentioning
confidence: 82%
“…4 A recent UK RCT in patients with a similar degree of treatment resistance as in the patients in this study (mean MGHS score of 4.7), although with a lesser severity of depression (baseline mean MADRS score of 28), reported a 21% response rate and a 16% remission rate after 5 weeks in patients treated with placebo or metyrapone DISCUSSION NIHR Journals Library www.journalslibrary.nihr.ac.uk augmentation of ongoing antidepressant treatment. 162 This suggests that patients in this study received considerable clinical benefit attributable to ECT treatment. However, the degree of improvement was less than is often reported with ECT; for example, Kellner et al 27 found a 65% remission rate with bilateral ECT, and a meta-analysis of seven cohort studies 8 found a 65% remission rate for patients without previous pharmacotherapy failure and a 48% remission rate for those with treatment resistance.…”
mentioning
confidence: 82%
“…One third were recruited as part of the above mentioned CFS study, with the remaining two thirds being recruited as healthy volunteers in a clinical trial investigating treatment-resistant major depression (McAllister-Williams et al, 2016). Recruitment for both studies happened during approximately the same time period.…”
Section: Methodsmentioning
confidence: 99%
“…These appear promising 178. Antiglucocorticoid compounds, including ketoconazole179 and metyrapone,180 have been investigated for depression, but both have drawbacks with their side effect profile and the clinical potential of metyrapone is uncertain. Mifepristone181 and the corticosteroids fludrocortisone and spironolactone,182 and dexamethasone and hydrocortisone183 may also be effective in treating depression in the short term.…”
Section: Future Prospectsmentioning
confidence: 99%